Meetings, negotiations, and socializing : a guide to professional english - Wallwork, Adrian (Guides to Professional English, 2014)
This book is a guide to taking part in meetings and negotiations, and to the socializing required before and after such events. If you are a non-native English speaker, with an intermediate level and above, and you work for a company with international relations, then this book is the solution to all your English problems! Four main topics are covered: 1.     Meetings 2.     Negotiations 3.     Socializing 4.     How to understand fast-speaking native English speakers This book is designed to be used like a manual or user guide - you don't need to read it starting from page 1. Like a manual it has lots of short subsections, and is divided into short paragraphs with many bullet points. This is to help you find what you want quickly and also to assimilate the information as rapidly and as effectively as possible. The book concludes with a chapter of useful phrases. There is an introduction for trainers on how to teach the skills required for meetings, negotiations and socializing in Business / Commercial English. Adrian Wallwork is the author of over 30 books aimed at helping non-native English speakers to communicate more effectively in English. He has published 13 books with Springer Science+Business Media.  Other books in this Professional English series: Email and Commercial Correspondence CVs, Resumes, and LinkedIn User Guides, Manuals, and Technical Writing Presentations, Demos, and Training Sessions Telephone and Helpdesk Skills